Uwarunkowania przyrodnicze w programowaniu rozwoju lokalnego - Legutko-Kobus, Paulina (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2010)
Sustainable development is based on equal treatment of social, economical and ecological aspects of development processes. Natural conditionings can be regarded by local communities both as an obstacle or as a stimulating factor of development. The article presents: analysis of the scope and context of taking into account the natural conditioning in local programming, comparative analysis of local documents regarding identification of natural environment values.